SCBMD: A knowledge-based system software for strategically correct bid/no bid and mark-up size decisions - Egemen, Mehmedali; Mohamed, Abdulrezak (Elsevier Science Bv, 2008)
This paper presents the development of a practical knowledge-based system software called SCBMD, which deals systematically with different bidding situations and assists the contractors in reaching 'strategically correct' bid/no bid and mark-up size decisions. The proposed framework differentiates among different sizes of contractors and uses a reasoning model that goes deeply into the heart of the decision making process. Hence, it helps to clarify the complex picture regarding the two sequential decisions and allows the users to follow the methodology used and the steps followed in reaching the final decisions. In order to see the degree to which SCBMD mirrors actual industry practices, it was implemented to 100 different real bidding situations. An accuracy of 86% was reached in simulating actual bid/no bid decisions of the contractors while the average difference in markup percentages proposed by the software and the contractors was found as 1.75%. Moreover, the software was evaluated for its timeliness under varying bidding conditions and found very effective especially for the cases where the contractor would like to reach decision alternatives for different possible scenarios of the same bidding situation. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: bidding strategy; bidding decision; mark-up; knowledge-based system; contractor